Los procedimientos internos de denuncia como medida de prevención de delitos en la empresa - Ragués i Vallès, Ramon (Revista Eletrônica de Direito Penal e Política Criminal, 2013)
The increasing desire of public authorities to turn citizens into informers of State (whistleblowers), encouraging those who may have knowledge of crimes to report them is a characteristic feature of contemporary criminal policy. The paper addresses this phenomenon and discusses its origins, its treatment in other countries that already have some tradition in its use and its growing international expansion. Then the question will be part of the new Spanish criminal justice system criminal of legal persons, without forgetting the impact that the issue may have for individuals. Finally it will be answered the question about the design that have to have these procedures if it is desired to obtain from them the benefits expected of a criminal decision.